The Making of middle Indonesia : middle classes in Kupang town, 1930s-1980s - Klinken, Geert Arend van (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 2014)
What holds Indonesia together? 'A strong leader' is the answer most often given. This book looks instead at a middle level of society. Middle classes in provincial towns around the vast archipelago mediate between the state and society and help to constitute state power. 'Middle Indonesia' is a social zone connecting extremes. This book examines the rise of an Indigenous middle class in one provincial town far removed from the capital city. Spanning the late colonial to early New Order periods, it develops an unusual, associational notion of political power. 'Soft' modalities of power included non-elite provincial people in the emerging Indonesian state. At the same time, growing inequalities produced class tensions that exploded in violence in 1965-1966.